LEADERSHIP STYLE, COMPETENCE, AND PROFESSIONALISM EFFECTS ON EMPLOYEE PERFORMANCE: EVIDENCE FROM INDRAMAYU DISKOMINFO - Yudha Indramawan; Weti Kurniawati; Ellin Herlina (PT. Berkah Digital Teknologi, 2026)
Purpose: To examine the effect of leadership style (X1), competence (X2), and professionalism (X3) on employee performance (Y) at the Department of Communication and Informatics of Indramayu Regency. Research Methodology: Quantitative survey; questionnaire (Likert scale 1–5); census sample (N=66); multiple linear regression; partial test (t-test); simultaneous test (F-test); coefficient of determination (R Square); normality test (Kolmogorov–Smirnov); multicollinearity test (Tolerance/VIF); software: IBM SPSS Statistics 27 for Windows. Results: Leadership style is significant (t=4.381; p=0.000) and competence is significant (t=2.152; p=0.035), while professionalism is not significant (t=0.059; p=0.953). The model is significant simultaneously (F=10.973; p=0.000). Model fit: R=0.589; R Square=0.347; Adjusted R Square=0.315. Limitations: Single-institution setting, one-time survey (cross-sectional), self-reported questionnaire data, and predictors limited to X1–X3 with N=66. Contribution: Useful for public-sector human resource management, leadership development, competency-based training, and performance improvement programs in government agencies, especially communication and informatics offices.